'Peace o'er the World': Village Carolling in the Hope Valley of Derbyshire. Issue 4 (2nd October 2022) - Russell, Ian
Abstract: The current traditions of Christmas carolling in the Derbyshire Peak District were well established by the end of the eighteenth century. The main centre of activity was and is the Hope Valley with its several settlements based on upland farming, small-scale industries, quarrying, and mineral extraction. These communities nurtured distinctive repertoires of local carols over two centuries and through into the twenty-first century. The research into this phenomenon draws on ethnographic fieldwork undertaken during the past fifty years and aims to understand it in terms of historical development, social context, performance dynamics, musical characteristics, and individual participation.